Spatial and seasonal variations of fine particle water-soluble organic carbon (WSOC) over the southeastern United States: implications for secondary organic aerosol formation - XL* Zhang; Z. Liu; Hecobian A; M* Zheng; NH Frank; Edgerton ES; Weber RJ (Atmos. Chem. Phys., 2012)
Secondary organic aerosol (SOA) in the southeastern US is investigated by analyzing the spatial-temporal distribution of water-soluble organic carbon (WSOC) and other PM2.5 components from 900 archived 24-h Teflon filters collected at 15 urban or rural EPA Federal Reference Method (FRM) network sites throughout 2007. Online measurements of WSOC at an urban/rural-paired site in Georgia in the summer of 2008 are contrasted to the filter data. Based on FRM filters, excluding biomass-burning events (levoglucosan < 50 ng m 3), WSOC and sulfate were highly correlated with PM2.5 mass (r2~0.7). Both components comprised a large mass fraction of PM2.5 (13% and 31%, respectively, or ~25% and 50% for WSOM and ammonium sulfate). Sulfate and WSOC both tracked ambient temperature throughout the year, suggesting the temperature effects were mainly linked to faster photochemistry and/or synoptic meteorology and less due to enhanced biogenic hydrocarbon emissions. FRM WSOC, and to a lesser extent sulfate, were spatially homogeneous throughout the region, yet WSOC was moderately enhanced (27%) in locations of greater predicted isoprene emissions in summer. A Positive Matrix Factorization (PMF) analysis identified two major source types for the summer WSOC; 22% of the WSOC were associated with ammonium sulfate, and 56% of the WSOC were associated with brown carbon and oxalate. A small urban excess of FRM WSOC (10%) was observed in the summer of 2007, however, comparisons of online WSOC measurements at one urban/rural pair (Atlanta/Yorkville) in August 2008 showed substantially greater difference in WSOC (31%) relative to the FRM data, suggesting a low bias for urban filters. The measured Atlanta urban excess, combined with the estimated boundary layer heights, gave an estimated Atlanta daily WSOC production rate in August of 0.55 mgC m 2 h 1 between mid-morning and mid-afternoon. This study characterizes the regional nature of fine particles in the southeastern US, confirming the importance of SOA and the roles of both biogenic and anthropogenic emissions.